Analisis Pengaruh Kualitas Pelayanan Jasa Puskesmas Terhadap Kepuasan Pasien di Puskesmas Pulorejo Kecamatan Ngoro - Sa'adah, Lailatus; Rahmawati, Ita; Arromlaty, Anis Laily Musyarofah (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to analyze the effect of service quality at Puskesmas Pulorejo, Ngoro District on patient satisfaction. Variables that affect patient satisfaction at Puskesmas Pulorejo, Ngoro sub-district are room facilities, doctor services, nurse / officer services. This study uses associative quantitative research methods. Data collection techniques in this study using questionnaires, observation and documentation. This data was obtained by distributing questionnaires directly to patients visiting the Pulorejo puskesmas in Ngoro sub-district. The population in this study were patients who sought treatment at the Pulorejo Health Center, Ngoro sub-district, sampling using purposive sampling. The analytical test tool in this study used SPSS with the analysis method of classical assumption test, multiple linear regression, hypothesis testing, and R2 determination coefficient test. In this study, it was stated that there was a positive and significant effect on patient satisfaction at the Pulorejo Health Center, the doctor's service variable had an effect on patient satisfaction, the nurse / officer service had a persial effect on patient satisfaction at the Pulorejo health center, and the variable room facilities, doctor services, and nurse / officer services had a positive and significant effect on patient satisfaction.